Randomized phase III study of docetaxel plus bavituximab in previously treated advanced non-squamous non-small-cell lung cancer. (14th May 2018) - Gerber, D E; Horn, L; Boyer, M; Sanborn, R; Natale, R; Palmero, R; Bidoli, P; Bondarenko, I; Germonpre, P; Ghizdavescu, D; Kotsakis, A; Lena, H; et al.
Abstract: Background: Bavituximab is a monoclonal antibody that targets phosphatidylserine in the presence of β2 glycoprotein 1 (β2GP1) to exert an antitumor immune response. This phase III trial determined the efficacy of bavituximab combined with docetaxel in patients with previously treated advanced non-small-cell lung cancer (NSCLC). Patients and methods: Key eligibility criteria included advanced non-squamous NSCLC with disease progression after treatment with platinum-based doublet chemotherapy, evidence of disease control after at least two cycles of first-line therapy, presence of measurable disease, ECOG performance status 0 or 1, adequate bone marrow and organ function, and no recent history of clinically significant bleeding. Eligible patients were randomized 1 : 1 to receive up to six 21-day cycles of docetaxel plus either weekly bavituximab 3 mg/kg or placebo until progression or toxicity. The primary end point was overall survival (OS). Results: A total of 597 patients were enrolled. Median OS was 10.5 months in the docetaxel + bavituximab arm and was 10.9 months in the docetaxel + placebo arm (HR 1.06; 95% CI 0.88–1.29; P  =   0.533). There was no difference in progression-free survival (HR 1.00; 95% CI 0.82–1.22; P  =   0.990). Toxicities were manageable and similar between arms. In subset analysis, among patients with high baseline serum β2GP1 levels ≥200 µg/ml, a nonsignificant OS trend favored the bavituximab arm (HR 0.82; 95% CI 0.63–1.06; P  =   0.134). Among patients who received post-study immune checkpoint inhibitor therapy, OS favored the bavituximab arm (HR 0.46; 95% CI 0.26–0.81; P  =   0.006). Conclusions: The combination of bavituximab plus docetaxel is not superior to docetaxel in patients with previously treated advanced NSCLC. The addition of bavituximab to docetaxel does not meaningfully increase toxicity. The potential benefit of bavituximab observed in patients with high β2GP1 levels and in patients subsequently treated with immune checkpoint inhibitors requires further investigation. Clinical trial number: NCT01999673.